Pengaruh Kepuasan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan: (Studi Kasus Pada CV. Global Jaya Sejahtera) - Putra, I Kadek Agus Candra; Wilyadewi, Ida I Dewa Ayu Yayati; Premayani, Ni Wayan Wina (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Human resources (HR) cannot be replaced by other resources in their roles and activities, so human resources are the main determining factor for companies. Employees are an important asset for the company, some argue that it is the employees who determine whether or not the company's goals are achieved. Decreased employee performance at CV. Global Jaya Sejahtera has attracted researchers to conduct research related to employee performance. The purpose of this research is to determine the effect of job satisfaction and workload on employee performance. The research method is quantitative with a saturated sampling method. The total sample used was 116 employees as research respondents. The results of this research are that job satisfaction has a partially positive and significant effect on employee performance, proven by tcount = 4.738>ttable = 1.658, so that H0 is rejected whereas H1 is accepted. Workload has a partially positive and significant effect on employee performance, proven by tcount = 8.218>ttable = 1.658, so that H0 is rejected whereas H2 is accepted. Simultaneously, job satisfaction and workload have a significant effect on employee performance, as evidenced by Fcount 55.282>Ftable 3.08, so that H0 is rejected whereas H3 are accepted. Based on the results, the coefficient of determination is 59.5%.